Capital adjustment costs: Implications for domestic and export sales dynamics - Yanping Liu (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2015)
Theoretical and empirical work on export dynamics has generally assumed constant marginal production cost and therefore ignored domestic product market conditions. However, recent studies have documented a negative correlation between firms' domestic and export sales growth, suggesting that firms can be capacity constrained in the short run and face increasing marginal production cost. This paper develops and estimates a dynamic model of export behavior incorporating short-term capacity constraints and endogenous capital investment. Consistent with the empirical evidence, the model features firms' sales substitutions across markets in the short term, and generates time-varying transition paths of firm responses through firms' capital adjustments over time. The model is fit to a panel of plant-level data for Colombian manufacturing industries and used to simulate how firm responses transition following an exchange-rate devaluation. The results indicate that incorporating capital adjustment costs is quantitatively important, as shown by the length of the transition period, and the difference between the short-run and long-run exchange rate elasticity of exports. Firms' expecation on the permanence of the policy changes also matters.
urn:nbn:de:bvb:19-epub-26600-3
Keywords: F12; L11; F14; 330; International trade; heterogeneous firms; capacity constraints; capital adjustment costs; firm dynamics; firm panel data